The Tiktok Application as a Digital Marketing Tool in the Bakeaway.id Cake Business - Meliana Dwi Puspita (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
At this time, marketing needs to utilize digital media in carrying out its marketing so that its market reach is wider to foreign countries. Marketing involved in digital media can enjoy special business advantages, both in terms of revenue, innovation, competitiveness, and employment opportunities. However, there are still many marketers who have not utilized technology through digital media and have not understood the magnitude of the benefits to be gained from the role of using digital media. One of the media that is often used in digital marketing is social media. The development of the world of digital marketing has been very rapid lately, one of which is on the tiktok platform. Now, they provide an online shop with the name tiktokshop, of course it is a new business opportunity for medium to lower level businesses, one of which is cakebakeway.id, a cake shop from Sokaraja Banyumas, Central Java, which utilizes the tiktokshop by becoming a seller in it with the tiktok algorithm which is very fast and broad in reaching all circles.